Efektivitas Whatsapp Group dalam Pembelajaran PAI secara Daring di SMP Negeri 5 Banguntapan Bantul - Salsabila, Unik Hanifah; Fauzi, Ismail; Sofi'i, Muhammad; Iyah, Silvi Al Patussifa; Ramadanti, Sintia (TSAQOFAH, 2022)
.As a result of the COVID-19 pandemic that hit, all educational institutions in Indonesia implemented distance learning online. Various learning media are the choices for use by various educational institutions during online learning. It also discusses in the learning process, each media has its own advantages and disadvantages. In online learning, especially in learning Islamic Religious Education. Whatsapp Group after going through various considerations, finally became the choice as an online learning medium by SMP Negeri 5 Banguntapan, Bantul in launching the process of teaching and learning activities. Although Whatsapp is the easiest and lightest medium to use, it also discusses when used in the online learning process there are various obstacles and learning becomes less than optimal. This article will discuss the effectiveness of Whatsapp Group in the process of online learning activities accompanied by various obstacles and conditions based on interviews and observations through direct observation in the learning process. So from the results of the study, the data can be seen to what extent the effectiveness of Whatsapp Group is and find solutions to problems and solutions to the factors and obstacles that hinder the learning process. WhatsApp has many features for sending messages, sending images, videos, sounds, creating groups and others and is easy to operate. The purpose of this study was to determine the effectiveness of online learning using WhatsApp media during the COVID-19 emergency in subjects. In an effort to reduce the spread of COVID-19 in schools.